2013
DOI: 10.1007/s12035-013-8522-7
|View full text |Cite
|
Sign up to set email alerts
|

Myoloid-Related Protein 8, an Endogenous Ligand of Toll-Like Receptor 4, Is Involved in Epileptogenesis of Mesial Temporal Lobe Epilepsy Via Activation of the Nuclear Factor-κB Pathway in Astrocytes

Abstract: The role of Toll-like receptor 4 (TLR4) in the activation of innate immunity has been extensively studied in the past several years. Here, we are the first to report that myeloid-related protein 8 (MRP8), an endogenous TLR4 ligand, is involved in the epileptogenesis of mesial temporal lobe epilepsy (MTLE). We find that the expression of MRP8, TLR4, and interleukin 1-β (IL-1β) was upregulated in a MTLE model during both acute and chronic disease stages. We next investigated the possible roles played by astrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 84 publications
1
17
0
Order By: Relevance
“…Observation in patients with focal cortical dysplasia [14] and SE [15] in rat models showed that there is activation of mammalian target of rapamycin (mTOR) and IL-1β in the brain. We have confirmed that inflammatory mediators such as Toll-like receptor 4, IL-1β, and nuclear factor kappa B expression were increased in MTLE rats and MTLE children [16,17] . It has been proven that IL-1β activates the PI3K/Akt signaling pathway after binding to its receptor [18] .…”
Section: Introductionsupporting
confidence: 68%
“…Observation in patients with focal cortical dysplasia [14] and SE [15] in rat models showed that there is activation of mammalian target of rapamycin (mTOR) and IL-1β in the brain. We have confirmed that inflammatory mediators such as Toll-like receptor 4, IL-1β, and nuclear factor kappa B expression were increased in MTLE rats and MTLE children [16,17] . It has been proven that IL-1β activates the PI3K/Akt signaling pathway after binding to its receptor [18] .…”
Section: Introductionsupporting
confidence: 68%
“…TLR 4 is target gene of CCAAT/enhancer binding protein delta which regulates inflammatory responses (Balamurugan et al, 2012) and modulates obesity-induced inflammation and insulin resistance (Jia et al, 2014) through PKC activation (Loegering and Lennartz, 2011), for example, PKC epsilon which may play a critical role in mediating fatinduced insulin resistance (Samuel et al,2007). Genetic variations of TLR-4 may be associated to bipolar disorder and epilepsy (Gan et al, 2013).…”
Section: Free Fatty Acids Activate Toll-like Receptorsmentioning
confidence: 99%
“…Metformin, GLP-I agonists and the other AMPK activators such as valproate, valsartan and the cannabinoid CB2 agonists may also downregulate Tolllike receptors and the High-Mobility Group Box-I protein (HMGBI) (Kovacs, 2012;Ha et al, 2014;Avery and Bumpus, 2013;Maroso et al, 2010;Gan et al, 2013); antagonise the cytokine, interleukin-I (Maroso et al, 201I;Vezzani et al, 2011;Roger et al, 2010;Suh et al, 2010); decrease advanced glycation end-products which is also associated with epilepsy, diabetes and drugs of abuse (Iori et al, 2013;Treweek et al, 2009) and upregulate BDNF (Whitfield et al, 2011;Hashimoto et al, 2002;Bovolenta et al, 2010) needed for attenuation of seizure progression and effects of microglia activation in diabetes and reward-related neuronal circuits. Additionally, via an AMPK-dependent mechanism, they may suppress matrix metalloproteinase-9 (MMP-9) which is upregulated in epilepsy (Wilczynski et al, 2008;Morizane et al, 2011;Esfahanian et al, 2012;Yin et al, 2011; and type 2 diabetes mellitus (Das and Maiti, 2013) and may be a potential new target in epilepsy treatment.…”
Section: Type 2 Diabetes Mellitus Drug Addiction Bipolar Disorder Amentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group is vigorously working to understand the mechanisms of many CNS diseases including meningitis [25][26][27] , intractable epilepsy [13,15,28] , and ischemic injuries [22] . Recent studies have shown that brain inflammation is an important factor contributing to almost all CNS diseases and activation of microglia is considered to be neuroinflammation hallmark.…”
Section: Research Highlightmentioning
confidence: 99%